EPCT-09. CLR 131 IN PATIENTS WITH RELAPSED OR REFRACTORY PEDIATRIC MALIGNANCIES. (4th December 2020) - Puccetti, Diane; Otto, Mario; Morgenstern, Daniel; DeSantes, Kenneth; Cho, Steven; Hall, Lance; Oliver, Kate; Longcor, Jarrod
Abstract: BACKGROUND: CLR 131 is a novel targeted radiotherapeutic that exploits the selective uptake and retention of phospholipid ethers by malignant cells. CLR 131 selectively delivers radiation to malignant tumor cells, thus minimizing radiation exposure to normal tissues. OBJECTIVE: CLR 131 is being examined in a Phase 1 trial, CLOVER-2 (NCT03478462), to determine the safety, tolerability, and initial efficacy of CLR 131 in children and adolescents with relapsed/refractory malignancies. METHODS: Eligibility criteria include children with relapsed or refractory solid tumors or malignant brain tumors for which there are no standard treatment options with curative potential. Subjects must be between ages 2 and 21 with no limit to the number of prior therapies. CLR 131 is administered as a single infusion in escalating doses beginning at 15 mCi/m 2 . Adverse events (AEs) are graded by NCI-CTCAE v5. RESULTS: As of 10Jan2020, four subjects with brain tumors have received CLR 131; one at 15 mCi/m 2 and three at 30 mCi/m 2 . Diagnoses included DIPG (2), glioblastoma (1), and medulloblastoma (1). Median age is 13 years (range 10–15) and patients received a median of two prior therapies (range 1 to 8). There were no treatment emergent AEs at the 15 mCi/m 2 dose level attributed to CLR 131 by the investigator. Assessment of the 30 mCi/m 2 dose level is ongoing. CONCLUSIONS: CLR 131 is a unique, first in class targeted radiotherapeutic for pediatric malignancies. Preliminary data shows an acceptable and expected safety profile in this patient population. Dose escalation to determine the highest tolerated dose is ongoing.